2023
DOI: 10.1002/dmrr.3747
|View full text |Cite
|
Sign up to set email alerts
|

A new declaration for feet's sake: Halving the global diabetic foot disease burden from 2% to 1% with next generation care

Peter A. Lazzarini,
Katherine M. Raspovic,
Marco Meloni
et al.

Abstract: The 1989 Saint Vincent Declaration established a goal of halving global diabetes‐related amputation rates. A generation later, this goal has been achieved for major but not minor amputations. However, diabetic foot disease (DFD) is not only a leading cause of global amputation but also of hospitalisation, poor quality of life (QoL) and disability burdens. In this paper, we review latest estimates on the global disease burden of DFD and the next generation care of DFD that could reduce this burden. We found DFD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 118 publications
0
7
0
Order By: Relevance
“…Diabetes is the most rapidly growing cause of the global disease burden [ 1 ], affecting an estimated 537 million people worldwide [ 2 , 3 ]. Diabetes-related foot ulcers are the leading cause of the global diabetes-related hospitalisations, amputations, and disease burden, affecting an estimated 20 million people yearly, with at least another 130 million people at risk [ 4 , 5 ]. These ulcers substantially reduce quality of life and impose a large disease burden on patients and society [ 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetes is the most rapidly growing cause of the global disease burden [ 1 ], affecting an estimated 537 million people worldwide [ 2 , 3 ]. Diabetes-related foot ulcers are the leading cause of the global diabetes-related hospitalisations, amputations, and disease burden, affecting an estimated 20 million people yearly, with at least another 130 million people at risk [ 4 , 5 ]. These ulcers substantially reduce quality of life and impose a large disease burden on patients and society [ 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes-related foot ulcers are the leading cause of the global diabetes-related hospitalisations, amputations, and disease burden, affecting an estimated 20 million people yearly, with at least another 130 million people at risk [ 4 , 5 ]. These ulcers substantially reduce quality of life and impose a large disease burden on patients and society [ 5 , 6 , 7 , 8 ]. Unfortunately, not all factors in the ulcer healing process are completely understood.…”
Section: Introductionmentioning
confidence: 99%
“…CNO has historically been considered a rare complication of diabetes, but recent studies suggest that the prevalence of CNO is substantially underestimated [ 4 ]. A novel analysis by Lazzarini et al underlined that 58% of the total global disease burden caused by Diabetic Foot Disease is the disability burden: this burden for the most part is at the expense of people with neuropathy without ulcers (thus including CNO) [ 5 ]. A nationwide cohort study conducted in Sweden showed the increasing prevalence of diabetic CNO from 0.55 to 0.79% (from 1.06 to 1.97% for type 1 diabetes) during the period 2006–2016 [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…1 In addition to these 21 publications that describe the presentday knowledge in diabetes-related foot disease, we also present 6 reviews from experts in the field in this special virtual issue. [23][24][25][26][27][28] These reviews aim to help guide the field forward, and discuss topics where the evidence may be thin, and where research and clinical practice can together advance the field and drive innovations.…”
mentioning
confidence: 99%
“…As a result of the ever-growing burden of both diabetes and diabetes-related foot disease, 25,29 continued efforts to improve remain needed. The unique multidisciplinarity of medical professionals involved in diabetes-related foot disease as shown in the list of 25 professions provided above requires huge collaborative efforts.…”
mentioning
confidence: 99%